Review of Early instructed second language acquisition: Pathways to competence; Editors: Joanna Rokita-Jaśkow, Melanie Ellis; Publisher: Multilingual Matters, 2019; ISBN: 9781788922494; Pages: 257 - Scheffler, Paweł (Studies in Second Language Learning and Teaching, 2019)
In a large scale survey of teachers’ perceptions of the challenges they face in teaching English to young primary school learners (Copland, Garton, & Burns, 2014), some of the key issues that are identified are as follows: teaching speaking, using only English in the classroom, enhancing motivation, maintaining discipline, catering for different individual needs (including special educational needs), dealing with parents, and teaching grammar as well as reading and writing. The relevance of Early Instructed Second Language Acquisition, edited by Rokita-Jaśkow and Ellis, is clearly shown by the fact that it addresses most of these central issues.